Comparison of Ethyl Acetate and Ethanol Solvents on Total Flavonoid Content from (Gnetum gnemon L.) Using UV-Vis Spectrophotometry - Panji Ratih Suci; Valiandri Puspadina; Andri Priyoherianto Andri Priyoherianto; Nurfitriawatie Nurfitriawatie; Fahmi Ardianti Purnawiranita; Achmad Misbakhul Maulana; Ach Zakyah Al Fauzi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Melinjo peel (Gnetum gnemon L.) is an agricultural by-product that is generally underutilized, despite its high content of flavonoid compounds with potential antioxidant activity. This study aimed to compare the effectiveness of ethanol and ethyl acetate as extraction solvents for flavonoids from melinjo peel based on differences in solvent polarity. Extraction was carried out using the maceration method, followed by quantitative analysis using spectrophotometry. Sample preparation involved drying and pulverizing the melinjo peel, extraction with ethanol and ethyl acetate at a material-to-solvent ratio of 1:10, phytochemical screening, thin-layer chromatography analysis, preparation of a quercetin calibration curve, and determination of total flavonoid content. Total flavonoid content was determined through the formation of a complex with aluminum chloride, and absorbance was measured at a wavelength of approximately 430 nm. Statistical analysis was conducted to evaluate differences between the two solvents. The results demonstrated that the ethanol extract produced a higher total flavonoid content (51.86 mg quercetin equivalent per gram of extract) compared to the ethyl acetate extract (46.05 mg quercetin equivalent per gram). The higher extraction efficiency of ethanol is attributed to its greater polarity, which enhances the solubilization of polar flavonoid compounds. In conclusion, ethanol is a more effective solvent than ethyl acetate for extracting flavonoids from melinjo peel, and these findings support the potential utilization of melinjo peel as a natural source of bioactive compounds for applications in the food, pharmaceutical, and cosmetic industries.